The impact of COVID-19 pandemic on physical and mental health among a sample of patients attending primary health centers in Erbil City - Hassan Ahmed , Zubaida; Hawez Sulaiman , Karwan (Diyala Journal of Medicine, 2023)
Background: Any pandemic is not only considered as a medical phenomenon; it has an impact on one’s life and its society. The impact of COVID-19 pandemic on physical and mental health is a common issue and up to the researcher’s knowledge, no previous study has been carried out among patients attending primary health care centers in Erbil City. Objective: To assess physical and mental health problems associated with Covid-19 pandemic among a Kurdish sample of patients. Patients and Methods: A cross sectional study using a convenience sample was conducted on 300 patients attending six primary health care centers in Erbil city. The study started from 1st of April 2021 to 31st of March 2022. The data were collected using a questionnaire after reviewing relevant literature. Results: The mean age (± S.D) of participants was 42.16 (±14.64) years, more than half (52.7%) of them were female, 65% of them were married. The majority (72.7%) of them were not smokers and 32.7% of them had chronic disease. More than half (61.7%) of participants stated that their physical activities were reduced and 38.3% of them gained weight. More than half (55.3%) of participants were infected with the Covid-19 while the rest (44.7%) were PCR negative with the disease. Thirty nine percent of participants suffered from sleep disturbance. There was significant statistical association between COVID-19 infection and gender, and marital status. There was non-significant statistical association between COVID-19 infection and sleep disturbance. Conclusion: Covid-19 pandemic had a significant impact on the participants’ wellbeing physically and mentally. Impact on physical health included decreased physical activities and weight gain and impact on mental health included psychological symptoms such as sleep disturbance, irritability, worry, feeling depressed, and insecurity about self and future.